1994
DOI: 10.1192/bjp.165.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Versus Out-Patient/In-Patient Care for People with Serious Mental Illness

Abstract: The loss of Phase I gains were perhaps due to attenuation of home-based care quality and to benefits of Phase I home-based care lingering into Phase II in DLP-controls. The Phase II home-based care team suffered from low morale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 5 publications
(1 reference statement)
1
47
1
3
Order By: Relevance
“…Toutefois, pour ce qui est de la satisfaction pour les autres aspects des services, les aidants dont le proche a utilisé uniquement les services dans la communauté manifestent une plus grande satisfaction que ceux dont le proche a fait appel à des services principalement offerts en milieu d'hospitalisation. Ces résultats s'apparentent à ceux décrits dans la littérature, où l'on observe que les services offerts à l'hôpital induisent des taux de satisfaction moins élevés que ceux offerts dans le cadre de services ambulatoires (Solomon et Marcenko, 1992 ;Audini et al, 1994). Il y a lieu de s'interroger sur les facteurs pou vant engendrer un degré d'appréciation moins élevé des services offerts en milieu hospitalier.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Toutefois, pour ce qui est de la satisfaction pour les autres aspects des services, les aidants dont le proche a utilisé uniquement les services dans la communauté manifestent une plus grande satisfaction que ceux dont le proche a fait appel à des services principalement offerts en milieu d'hospitalisation. Ces résultats s'apparentent à ceux décrits dans la littérature, où l'on observe que les services offerts à l'hôpital induisent des taux de satisfaction moins élevés que ceux offerts dans le cadre de services ambulatoires (Solomon et Marcenko, 1992 ;Audini et al, 1994). Il y a lieu de s'interroger sur les facteurs pou vant engendrer un degré d'appréciation moins élevé des services offerts en milieu hospitalier.…”
Section: Discussionunclassified
“…Les résultats des études effectuées permettent de constater que les familles sont généralement moins satisfaites des services de santé mentale que leurs proches (Rugerri et al, 1994) et que le degré de satisfaction des familles est moins élevé pour ce qui est des services offerts à l'hôpital, que pour ceux offerts dans la communauté (Solomon et Marcenko, 1992 ;Marks et al, 1994 ;Audini et al, 1994). Selon certains auteurs (Grella et Gruski, 1989 ;Solomon et Marcenko, 1992 ;Hanson, 1995 ;Leavy et al, 1997), les contacts qu'ont les familles avec les intervenants seraient un des points majeurs d'insatisfaction.…”
Section: Remerciementsunclassified
“…This analysis concluded that costs incurred by the DLP were lower than those of the hospital-based alternative leading the authors to conclude that the community-based programme was more cost-effective. However, after four years all of the clinical gains, as well as the cost advantage, that the DLP had were lost (Audini et al, 1994;Knapp et al, 1997).…”
Section: Cost-effectiveness Of Crisis Interventionmentioning
confidence: 99%
“…The results revealed that the DLP programme produced more favourable outcomes and greater patient and family satisfaction than its comparator. The costs of the DLP were also compared with traditional hospital-based care (Marks et al, 1994;Knapp et al, 1994). Three main cost categories were considered: services used in the treatment and support of patients, lost employment opportunities and the burden of informal care.…”
Section: Cost-effectiveness Of Crisis Interventionmentioning
confidence: 99%
“…Several studies have noted that length of hospital stay returned to pre-intervention levels when the ACT team was withdrawn or when their control of discharge was blocked by hospital authorities (Test et al, 1991;Audini et al, 1994). At least one well-conducted controlled trial has found ACT to be superior to other models of intensive case management in reducing hospital utilisation (Essock & Kontos, 1995).…”
Section: Only Act Models Consistently Decrease the Use Of In-patient mentioning
confidence: 99%